Estimating deaths due to other infectious diseases in Thailand 1996-2009 based on 2005 Verbal Autopsy data - Wattanavadee Sriwattanapongse (Faculty of Medicine, Chiang Mai University, 2019)
Chiang Mai Medical Journal (Formerly Chiang Mai Medical Bulletin) is an official journal of the Faculty of Medicine, Chiang Mai University. It accepts original papers on clinical and experimental research that are pertinent in the biomedical sciences. The Journal is published 4 issues/year (i.e., Mar, Jun, Sep, and Dec).